PENGARUH KANDUNGAN MINYAK DAN DETERJEN DALAM AIR CAMPURAN BETON TERHADAP KUAT TEKAN - TAPAYASA, IM; BUDIARSA SUYASA, IW.; ADHIKA, IMD. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 3 No 1)
The concrete represent materials/rock that is yielded by mixing smooth aggregate (sand), harsh aggregate (gravel), water and portland cement according to Regulation of Reinforced Concrete Indonesia (PBI) 1971 NI-2. Detergent concentraton (LAS) and Diesel fuel, LAS + Diesel fuel was added in each treatment of 0%; 1 ; 2,5 ; 5% to mixed water until attain minimum standard of depress strength according to SNI. From result of research revealed that content of LAS 0,3 % aftarned depress strength concrete equal to 23,578 Mpa at 7 day and 28,654 Mpa at 28 day according to minimum requiretment of SNI with ercentage equal to 90,24 % and 89,67 %. With Diesel fuel content 5 % afterned depress concrete strength equal to - 23,536 Mpa at 7 day and 28,717 Mpa at 28 days according to minimum requitement of SNI with percentage equal to 90,08 % and 89,87 %. With mixture content of LAS and Diesel of fuel 0,2% afterned depress concrete strength equal to 23,610 Mpa at 7 days and 28,698 Mpa at 28 days according to minimum reqirement of SNI with percentage equal to 90,36 % and 89,81 %.
Keywords: LAS, Diesel Fuel, an mixed water, Concrete Depress Strength.